KEMITRAAN PEMERINTAH DAN SWASTA DALAM KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA PEKANBARU - ', Isril; Febrina, Rury; Harirah, Zulfa (Universitas Riau, 2018)
The partnership between the Regional Government and the private sector is a step that the Government can take as an effort to cover up the limitations in waste management in the city of Pekanbaru. The dynamics of rapid population growth have had consequences for increasing the volume of garbage to approximately 1,100 tons per day. The Pekanbaru City Government then took steps to implement partnerships with the private sector as an effort to manage waste management. However, the involvement of the private sector in dealing with waste issues actually showed a failure in 2015. In 2018, the Pekanbaru City Government again planned to submit waste management to the private sector. Therefore, this study tries to focus on two formulations of the problem, which is why the Pekanbaru City Government again delegates the authority to manage waste in the city of Pekanbaru to the private sector? And what is the right scheme for government and private partnerships in carrying out waste management in Pekanbaru City? To answer the above questions, this research was escorted by the Reinventing Government theory of David Osborne and Ted Gaebler and also the theory of Public Private Partnership. Through the case study method, this research will explore the partnership between Pekanbaru City Government and the private sector in waste management in Pekanbaru City. The results showed that the objective of the partnership between the Regional Government of Pekanbaru and third parties in waste management in the city of Pekanbaru was to overcome the inability of the Pekanbaru City Government to provide facilities and infrastructure, garbage fleets, human resources and budget constraints. Thus, the logic of this partnership leads to one of the lines of thought offered by Osborn regarding the Catalytic Government (Steering Rather Than Rowing). The scheme of success of the partnership of Pekanbaru City Government and the private sector in waste management needs to pay attention to process factors, partner factors and structural factors. Thus, waste management in the city of Pekanbaru requires a paradigm shift, from being limited to disposal to become a focus on management and utilization.